IMPLEMENTASI KEBIJAKAN IDENTITAS KEPENDUDUKAN DIGITAL (IKD) DALAM PENERBITAN ADMINISTRASI KEPENDUDUKAN DIGITAL DI KECAMATAN BUMI WARAS KOTA BANDAR LAMPUNG - Rizke Hulan Djano; Eny Inti Suryani; Putri Rahmaini (AS-SIYASAH : Jurnal Ilmu Sosial Dan Ilmu Politik, 2024)
The aim of this research is to analyze the implementation of the Minister of Home Affairs Regulation Number 7 of 2019 concerning the Implementation of Online Population Administration in Bumi Waras District. This research also aims to explain problems that arise in its implementation, as well as provide recommendations for improvements that can increase the efficiency and effectiveness of population services.This research uses a descriptive qualitative approach. Primary data was obtained through interviews and observations with users of population administration services, both through applications and websites. Secondary data was obtained through literature study and document study related to Permendagri guidelines and other related policies. The data analysis method involves data reduction, data presentation, as well as drawing conclusions and verification.The research results show that the implementation of ImplementasiKependudukan Digital (IKD)  in Bumi Waras District is carried out through the "Digital Population Identity" application which allows online registration and verification. This online service involves the use of the Population Administration application and website in accordance with the guidelines of Minister of Home Affairs Regulation No. 7 of 2019. Even though there are several challenges, such as public awareness and investment in cyber security, the implementation ofIdentitasKependudukan Digital (IKD) has had a positive impact in the form of increasing efficiency, speed and accessibility of population services.